Apoptosis and genotoxicity effects of Zygophyllum album and Suaeda palaestina extracts on Ehrlich solid carcinoma in mice - Marwa M. El-Attar; Ekram S. Ahmad; Hedaya A. Kamel; Amal I. Hassan; Abdel-Fattah A. Awad; Fatthy M. Abdel-Tawab (Bulletin of the National Research Centre)
Abstract Background Various medicinal plants and their bioactive compounds exhibited promising anticancer activities by inducing apoptosis, inhibiting angiogenesis, and modulating several signaling pathways in cancer cells. This study aims to assess whether two medicinal plant extracts have anticancer properties, Suaeda Palaestina and Zygophyllum album. Methods This study used Ehrlich solid tumor mice as its in vivo model. We divided male mice into five groups (n = 5 per group). Group I was used as a control for Ehrlich ascites carcinoma (EAC). Groups 2 and 3 were given Z. album extract 180 mg/kg and 360 mg/kg body weight intraperitoneally. Groups 4 and 5 were given the same dose of S. palaestina and treated three times a week for 2 weeks, starting on day 10 after EAC implantation. After 3 weeks, we collected blood samples and thigh skeletal muscle, homogenized them, and processed them for analysis. The results showed that Ehrlich solid rats (EST) treated with low-dose dichloromethane extracts from Z. album and S. palaestina had significantly smaller tumor sizes than the control group. Protein expression levels of p53, caspase 3, and Bcl-2 were quantified by western blotting. Results The extracts from both plants induced the hunger mechanism, leading to increased expression of p53 and caspase 3 and decreased expression of Bcl-2 at the protein level in EST mice treated with Z. album and S. palaestina. In addition, the comet assay indicated that these plants have a genotoxic potential for solid tumor cells. The T3 and T4 levels in EST blood samples revealed that both plants had significantly reduced the concentration of T3 and significantly increased T4 compared to the EST mice untreated group. Furthermore, these results showed that Z. album and S. palaestina had antiproliferative effects in EST mice through apoptosis-mediated genotoxicity. Conclusions These findings indicated that S. palaestina and Z. album could be considered potential natural sources of anticancer agents.